Study on the Equilibrium Discriminant Model of Urban Agglomeration Transport Supply and Demand Structure - Z. Y. Liu; C. B. Li; M. Y. Jian (Journal of Advanced Transportation)
In order to study the adaptability of urban agglomeration transport supply and demand structure, and to provide the basis for decision-makers when optimizing the structure of transport supply and demand in urban agglomeration, this paper proposed and verified a structure equilibrium theory on the basis of entropy theory. Firstly, based on the analysis of the influencing factors, an urban agglomeration transport demand structure model was established using entropy theory. Secondly, according to the actual passenger and freight turnover of urban agglomeration, a transport supply structure model was proposed with entropy theory. Then, by comparing the two entropy models, the equilibrium state of an urban agglomeration transport structure was analyzed. Finally, HuBaoOr urban agglomeration was taken as an example to verify the science and effectiveness of this discriminant model. The research in this paper lays a theoretical foundation for the achievement of urban agglomeration transport equilibrium structure and for realizing the best economic benefits and social benefits.